Vitamin D(3) Therapy Corrects the Tissue Sensitivity to Angiotensin II Akin to the Action of a Converting Enzyme Inhibitor in Obese Hypertensives: An Interventional Study - Vaidya, Anand (Endocrine Society, 2012)
CONTEXT: Vitamin D deficiency and obesity are associated with increased tissue renin-angiotensin system (RAS) activity. OBJECTIVE: The objective of the study was to evaluate whether vitamin D(3) therapy in obesity reduces tissue-RAS activity, as indicated by an increase in tissue sensitivity to angiotensin II (AngII). PARTICIPANTS: Participants included obese subjects with hypertension and 25-hydroxyvitamin D less than 25 ng/ml. DESIGN: Subjects were studied before and after 1 month of vitamin D(3) 15,000 IU/d, while in dietary sodium balance, and off all interfering medications. Fourteen subjects successfully completed all study procedures. SETTING: The study was conducted at a clinical research center. OUTCOME MEASURES: At each study visit, tissue sensitivity to AngII was assessed by measuring renal plasma flow (RPF), mean arterial pressure (MAP), and adrenal secretion of aldosterone during an infusion of AngII. Subjects were then given captopril, and a second AngII infusion to evaluate the effect of captopril on tissue-RAS activity. RESULTS: Vitamin D(3) therapy increased 25-hydroxyvitamin D (18 to 52 ng/ml) and basal RPF (+5%) and lowered supine MAP (−3%) (all P < 0.01). There was a greater decline in RPF and higher stimulation of aldosterone with AngII infusion after vitamin D(3) therapy (both P < 0.05). As anticipated, captopril increased the renal-vascular, MAP, and adrenal sensitivity to AngII, but this effect was much smaller after vitamin D(3) therapy, indicating that vitamin D(3) therapy corrected the tissue sensitivity to AngII akin to captopril. CONCLUSIONS: Vitamin D(3) therapy in obese hypertensives modified RPF, MAP, and tissue sensitivity to AngII similar to converting enzyme inhibition. Whether chronic vitamin D(3) therapy abrogates the development of diseases associated with excess RAS activity warrants investigation.